Advances in volumetric ultrasound applications in gynecology and obstetrics - Huamán, Moisés (2015)
In the last decade we have seen important advances in ultrasound volumetric software. Specific programs for new applications have been obtained by improving volume capture, presentation and management processes. We review in this paper physics of 3D-4D volumetric ultrasound and the new technology application in  Gynecology, Obstetrics and human reproduction.